China’s Alternate Gaze towards the Indo-Pacific (The Strategic Review for Southern Africa, 2022)
China’s perspective of the Indo-Pacific, as a set of strategies initially developed by Japan but mainly driven by the United States (US), appears to be shifting. Beijing originally viewed such approaches as directly countering its influence in the mega-region of the same name. Yet more recently, China has made pronouncements that seem to suggest its relative support of particular state and regional organisation’s Indo-Pacific strategies. This article explores this changing perspective, and the dilemmas facing China as a rising global power in a liberal international order through the lens of strategic narratives. On the one hand China understands that it needs to engage the global system and cannot isolate from it, and at the same time, Beijing seeks to challenge the US-led liberal international order to achieve its ambitions. This dual approach is explained through China’s use of alternative diplomacy and is further explored through two examples. The first is China’s engagement in the Western Indo-Pacific and specifically Africa (an emphasis of this journal volume), where it remains a strategic partner in the political and tangible economic sense. Secondly, at the conceptual level, the Indo-Pacific is not yet an institutionalised concept, and its contours and future are left open to interpretation. Since allegiances and interests are shifting, China has the opportunity to contribute to the very ideas and norms that inform what the ‘Indo-Pacific’ means in ways that can further its own strategic interests.